Biodiversity of Fresh Water Algae from Temple Tanks of Kerala - Nagaraj1; Narayanswamy Anand1,2, Pathmanapan Arulmurugan1, Subramani (Recent Research in Science and Technology, 2010)
Algal samples were collected from 37 temple-tanks in Palakkad and Thrissur district in Kerala. Collections were carried out during the month of March 2008 and May 2009. Samples were studied in the laboratory and identified. The following algae were present Pandorina cylindricum, Chlorococcum humicolo, Botryococcus braunii, Chlorella vulgaris, Golenkinia radiata, Tetraedron octaedricum (Reinsch) Hansgirg Var. spinosum, Ankistrodesmus fulcatus, Ankistrodesmus spiralis, Westella linearis, Selenastrum minutum, Kirchneriella lunaris, Pediastrum simplex Meyen var. duodenarium, P. simplex Meyen var. simplex, P. duplex, P. duplex Meyen var. genuinum, P. duplex Meyen var. reticulatum, P. tetras, P. tetras (Ehrenberg) Ralfs var.excisum, P. tetras (Ehrenberg) Ralfs var. tetraodon, Coelastrum microporum, Crucigenia tetrapedia, Tetrastrum heteracanthum, Scenedesmus acuminatus, S. armatus, S. denticulatus, S. longus Meyen var. naegeli, S. opoliensis, S. perforatus Lemm. var. major, S. quadricauda (Turpin) Brebisson var. maximum, S. quadricauda (Turpin) Brebisson var. quadrispina, Netrium elongatum, Spirogyra hyalina, Closterium decorum, Closterium setaceum, Cosmarium impressulum, C. portianum Arc. var. nephroides, Staurastrum spiniceps Krieg var. trifidum (Chlorophyceae), Cyclotella magneghiniana, Melosira granulata, Fragillaria brevistriata, Synedra dorsiventralis, Navicula radiosa, Cymbella kolbei, C. tumescens, Pinnularia abanjensis, Gomphonema lanceolatum, Amphora coffeaformis (Bacillariophyceae), Euglena proxima, Phacus leuronectes (Euglenophyceae), Microcystis robusta, M. viridis, M. wesenbergii, Chroococcus indicus, Merismopedia punctata, Hydrococcus rivularis, Spirulina gigantea, Oscillatoria chalybea, Phormidium aerugineo - coeruleum, Lyngbya lutea, Anabaena sphaerica, Westiellopsis prolifica (Cyanophycaeae). Algae are described with photographs.